2019
DOI: 10.3390/catal9110886
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diesel and Jet Fuel Range Cycloalkanes with Cyclopentanone and Furfural

Abstract: Diesel and jet fuel range cycloalkanes were obtained in~84.8% overall carbon yield with cyclopentanone and furfural, which can be produced from hemicellulose. Firstly, 2,5-bis(furan-2-ylmethyl)-cyclopentanone was prepared by the aldol condensation/hydrogenation reaction of cyclopentanone and furfural under solid base and selective hydrogenation catalyst. Over the optimized catalyst (Pd/C-CaO), 98.5% carbon yield of 2,5-bis(furan-2-ylmethyl)-cyclopentanone was acquired at 423 K. Subsequently, the 2,5-bis(furan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…The hydrogenation of furfural to cyclopentanone, for the efficient utilisation of biomass-derived chemicals has been presented [83]; cyclopentanone is a versatile chemical compound that finds numerous applications in several industries such as in the pharmaceuticals and rubber sector [84]. Furthermore, recent past studies, has demonstrated the production of high yield diesel and jet fuel range alkanes from furfural, reinforcing the opportunities and possibilities that furan-based chemicals afford us in the quest for sustainable chemical feedstock, fuel and energy [85,86].…”
Section: Selected Uses/applicationsmentioning
confidence: 99%
“…The hydrogenation of furfural to cyclopentanone, for the efficient utilisation of biomass-derived chemicals has been presented [83]; cyclopentanone is a versatile chemical compound that finds numerous applications in several industries such as in the pharmaceuticals and rubber sector [84]. Furthermore, recent past studies, has demonstrated the production of high yield diesel and jet fuel range alkanes from furfural, reinforcing the opportunities and possibilities that furan-based chemicals afford us in the quest for sustainable chemical feedstock, fuel and energy [85,86].…”
Section: Selected Uses/applicationsmentioning
confidence: 99%
“… 115 Cycloalkanes were produced in two steps in ∼84.8% overall carbon yield starting from CPN and FF. 116 In the initial step, 2,5-di(furylmethyl)cyclopentanone (DFMCPN) was prepared in a 98.5% yield by the aldol condensation/hydrogenation reaction of CPN and FF using Pd/C–CaO as a solid bifunctional base as well as a hydrogenation catalyst. In the final step, DFMCPN was subjected to HDO chemistry over the Pd/H-ZSM-5 catalyst under solvent-free conditions to provide cycloalkanes in 86.1% yield.…”
Section: Applications Of Cpn and Hcpnmentioning
confidence: 99%
“…Recently, bimetallic FeNi 3 NPs enriched with Ni (FeNi 3 @Ni) have been used as catalysts as well as magnetic heating agents for the oligomerization of CPN to yield C 10 and C 15 oligocyclopentyl products . Cycloalkanes were produced in two steps in ∼84.8% overall carbon yield starting from CPN and FF . In the initial step, 2,5-di­(furylmethyl)­cyclopentanone (DFMCPN) was prepared in a 98.5% yield by the aldol condensation/hydrogenation reaction of CPN and FF using Pd/C–CaO as a solid bifunctional base as well as a hydrogenation catalyst.…”
Section: Applications Of Cpn and Hcpnmentioning
confidence: 99%
“…Highdensity biofuel was synthetized using hydroxyl alkylation/ alkylation of cyclopentanone/cyclohexanone and furfural. Wei Wang, et al, [13][14][15][16][17] reported renewable diesel were obtained with 2methylfuran and angelica lactone under catalysts for the reaction include Naon212, Amberlyst-36 and Amberlyst-15 resin. However, the high cost of Naon212 resins may limit their use in industrial scale.…”
Section: Introductionmentioning
confidence: 99%